Does Fibre-fix provided to people with irritable bowel syndrome who are consuming a low FODMAP diet improve their gut health, gut microbiome, sleep and mental health? A double-blinded, randomised controlled trial. Issue 1 (17th August 2020) - Yan, Ran; Murphy, Mandy; Genoni, Angela; Marlow, Evania; Dunican, Ian C; Lo, Johnny; Andrew, Lesley; Devine, Amanda; Christophersen, Claus T
Abstract : Introduction: A diet low in fermentable oligosaccharides, disaccharides, monosaccharides and polyols (FODMAP) is an effective way to reduce gut symptoms in people with irritable bowel syndrome (IBS). This diet reduces the intake of fermentable fibres, leading to changes of the gut microbiota and insufficient fermentation in the large bowel, resulting in reduced production of short-chain fatty acids (SCFAs), such as butyrate, which has unfavourable implications for gut health, sleep and mental health. This study will examine the effect of Fibre-fix, a supplement containing a mix of dietary fibres, on the human gut microbiome composition, fermentative capacity, sleep, quality of life (QOL) and mental health of people with IBS who consume a low FODMAP diet (LFD). Methods and analysis: A randomised, double-blind, placebo-controlled, study design is proposed to examine whether Fibre-fix added to an existing LFD may help modulate gastrointestinal function, improve markers of sleep, mental health and promote QOL in patients with IBS. Participants will provide stool and blood samples, daily bowel symptoms diaries and 3-day diet records. Additionally, they will complete validated questionnaires relating to FODMAP intake, sleep, mental health and QOL before and after a 3-week intervention. Gut health will be assessed via faecal microbiome composition, faecal pH and SCFA levels. Alteration of sleep will be recorded using an actigraphy device worn by all participants over the whole study. Multivariate analysis will be used to examine the gut microbiome and repeated measures Analysis of variance (ANOVA) will be used for dependent variables from questionnaires related to bowel symptoms, stool type, sleep, mental health and QOL to assess the differences between intervention and control groups after adjustment for confounding variables. Ethics and dissemination: Ethics approval was obtained from the Human Research Ethics Committee of Edith Cowan University (2019-00619-YAN). Results will be disseminated in peer-review journal publications, and conference presentations. Participants will be provided with a summary of findings once the study is completed. If Fibre-fix is shown to result in favourable changes in gut microbial composition, SCFA production, sleep and mental well-being without exacerbating symptoms, this will provide additional dietary management options for those with IBS following an LFD. Trial registration number: ACTRN12620000032954.